Acute Fatty Liver of Pregnancy Management in Intensive Care - Atsari, Nadhila; Apsari, Ratih Kumala Fajar; Adiyanto, Bowo; Widodo, Untung (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2026)
Background: Acute fatty liver of pregnancy (AFLP) is an obstetric emergency with high mortality that usually requires treatment in the intensive care unit (ICU). The cause of AFLP is not known with certainty, but it is suspected due to a deficiency of long chain 3-hydroxyacyl CoA dehydrogenase (LCHAD) in the fetus which causes accumulation of fatty acid metabolites from the fetus and placenta which are hepatotoxic. The clinical manifestations of AFLP are acute liver failure and progression to multiple organ dysfunction syndrome (MODS). This reported case was the only one successful case out of 3 incidences of AFLP recorded in RSUP Dr. Sardjito Yogykarta within a year of 2022. Case Illustration: A 24-years-old postpartum woman at 38 weeks' gestation admitted to resuscitation room with hypovolemic shock due to early postpartum hemorrhage. Patient was resuscitated and then taken to emergency operating room for uterine exploration under general anesthesia. Patient was subsequently admitted to the intensive care unit (ICU). The patient's initial condition was intubated, requiring vasopressor support with epinephrine and norepinephrine, and the patient showed symptoms of encephalopathy, liver failure and kidney failure. AFLP diagnosis was then made with patient showing score 10 of Swansea criteria. Resuscitation, stabilization, and intensive care treatment was continued for up to eight days in the ICU. The patient's final condition was stable, there were no sequelae of AFLP and the patient was discharged from the hospital at the 14th day in good condition.Conclusion: AFLP is a serious complication during pregnancy and postpartum period that is reversible with a chance of complete recovery but has a high mortality associated with delayed treatment. Adequate early intensive care treatment with multidisciplinary approach essential for successful treatment of AFLP.